Deduct it! : lower your small business taxes - Fishman, Stephen, frey50 (California Nolo, 2016)
Fishman provides information for maximizing business deductions. Whether your enterprise is just starting or well established, this book is indispensable to your financial success.
Tax deduction basics -- Are you really in business? -- Start-up expenses -- Business operating expenses -- Deducting long-term assets -- Inventory -- Office expenses -- Car and local travel expenses -- Business travel -- Meal and entertainment expenses -- Hiring workers -- Retirement deductions -- Medical expenses -- Additional deductions -- Record keeping and accounting -- Claiming tax deductions for prior years -- Staying out of trouble with the IRS -- Help beyond this book.
Tax deduction basics -- Are you really in business? -- Start-up expenses -- Business operating expenses -- Deducting long-term assets -- Inventory -- Office expenses -- Car and local travel expenses -- Business travel -- Meal and entertainment expenses -- Hiring workers -- Retirement deductions -- Medical expenses -- Additional deductions -- Record keeping and accounting -- Claiming tax deductions for prior years -- Staying out of trouble with the IRS -- Help beyond this book.
Includes index.
Keywords: Small business -- Taxation -- Law and legislation -- United States; Tax deductions -- United States; Small business -- Taxation -- Law and legislation; Tax deductions; Tax planning -- United States; United States; Popular works; Law for laypersons